Dynamic costs of soil degradation and determinants of adoption of soil conservation technologies by smallholder farmers in Malawi - Hassan, Rashid M. (University of Pretoria, 2013)
Thesis (PhD (Agricultural Economics))--University of Pretoria, 2006.